KRITIK SOSIAL DALAM IKLAN SAMPOERNA A MILD VERSI “BUKAN MAIN” (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - Annisa, Fiqa; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Cigarette advertisements are packaged differently because of regulations regarding the broadcasting rules. Advertisers are required to be creative in making advertisements so that they do not violate the established regulations, by only displaying brand images without clearly showing their products. The images commonly displayed in cigarette advertisements are lifestyle, passion, and masculinity, but different from the usual version of Sampoerna A Mild advertisement, it was found to raise issues of social reality and criticize mass cultural deviations and social problems. This study uses a qualitative approach with descriptive methods and uses the semiotic theory of Charles Sanders Peirce, to find out the meaning of social criticism in the Sampoerna A Mild advertisement version of Bukan Main. The results of this study indicate that this advertisement criticizes three of the eight social problems that occur in the community, namely violations of norms, crime and also environmental problems. Keywords: Advertising, Sampoerna A Mild, Semiotics, Social Criticism, Social Problem